POLITIK HUKUM PEMERINTAH DALAM BIDANG PERTANAHAN DARI PERSPEKTIF HAK ASASI MANUSIA - Muhammad Halwan; Almusawwir Nansa (MADDIKA : Journal of Islamic Family Law, 2021)
This study aims to determine the legal politics of the government in the land sector from a human rights perspective. The research results were obtained through normative legal research by examining library materials or secondary data as well as legal developments that support  the  research.  The  results  of  this  study  indicate  that  individual  property  rights  arise from the relationship between humans and nature, not from human-human relations. Property rights  do  not  depend  on  the  consent  of  others,  but  arise  because  of  individual  businesses. Property  rights  are  natural  rights  that  do  not  originate  from  the  state,  are  managed individually and must be protected by the state. Land ownership rights can also be said to be human  rights,  not  because  of  inherent  rights  to  humans,  but  natural  rights  obtained  from human struggles or efforts. Thus, the revocation or relinquishing of land rights from private property by force is a violation of human rights. Citizens' refusal to implement various laws and  regulations  in  the  land  sector  is  evidence  that  government  policies  in  the  land  sector, both at the substance or content level (het onderwerp) of the prevailing laws and regulations, have not shown serious attention to guarantee and protection of human rights.